Активність дихальних процесів у плодах томата при зберіганні за дії антиоксидантів - Прісс, Олеся Петрівна; Присс, Олеся Петровна; Priss, Оlesia; Жукова, Валентина Федорівна; Жукова, Валентина Федоровна; Zhukova, Valentina (My University, 2011)
EN: During the research into dynamics of respiration intensity, total content of dry matter, pectin substances, sugars, acidity in tomato fruits during storage with antioxidants it was proved that treatment of tomato fruits with antioxidants and artificial cold makes it possible to slow down the respiration processes in fruits, which facilitated prolongation of their qualitative storage terms.
Keywords: elaterids; insecticide protectants; action efficiency; economic efficiency; tomatoes; storage; antioxidants; respiration intensity; respiration substratum